MODEL INTEGRASI SISTEM PENDIDIKAN DAYAH SALAFIYAH - Saifuddin (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2022)
Dayah salafiyah today has adopted a lot of national education systems, with their own systems and models. The idea of ​​the Islamic Islamic boarding school integration model through the existence of schools and madrasas is the focus of this research. The subjects of the dayah that were chosen were the Darusa'adah Teupin Raya dayah, which has a high school; Dayah Jeumala Amal, which has a madrasah system, and dayah Ummul Ayman, which has a vocational-based school (SMK). The focus of the problem is, what is the form of integration of the Islamic boarding school education system through schools and madrasas? This research is called qualitative research. The author collects data through observation, interviews, and documentation studies at the three Islamic boarding schools. Data analysis consists of; data reduction, data presentation, and conclusion drawing. The results showed that the forms of integration of the Islamic education system through SMA in Dayah Darussa'adah were scientific integration, informal integration of curriculum, and integration of akhlakul karimah values. The form of integration of dayah education through Dayah Jeumala Amal is integration of scientific correlation, extracurricular integration, and integral-formal, and holistic integration. As for the integration of Dayah Ummul Ayman 3 education with Vocational High School, namely correlation-informal integration, and integration of religion with entrepreneurship.